Road Safety Audit Tangerang - Merak Toll Road - Agus Lutfi; Bambang Riyanto; Bambang Haryadi (Eduvest - Journal of Universal Studies, 2024)
Tangerang-Merak Toll Road is a toll road connecting Tangerang and Merak Port, which includes Cikupa Toll Road, East Balaraja, West Balaraja, Ciakande, Ciujung, East Serang, West Serang, East Cilegon, West Cilegon, and Merak. With the more congested, will make the risk of car accidents also increased. In an effort to improve of road safety, especially toll roads, a Road Safety Audit (AKJ) is needed. Aspects examined and observed include geometric, traffic management, pavements, street furnitures and complementary buildings. As a result, it is concluded that in geometric aspect, in general has been designed in accordance with the provisions, but nevertheless there are parts that still require improvement. This research will discussed the existing condition of Tangerang-Merak Toll Road based on direct observation. The aspects reviewed are geometric, pavement, street furnitures and road complementary buildings such as Signs, Markings and Median roads. In the end, accident-prone areas will be obtained on tangerang- merak toll road with a comparison analysis of direct observation data, and traffic accident data.